The discovery and characterization of AeHGO in the branching route from shikonin biosynthesis to shikonofuran in Arnebia euchroma - Wang, Ruishan; Liu, Changzheng; Lyu, Chaogeng; Sun, Jiahui; Kang, Chuanzhi; Ma, Ying; Wan, Xiufu; Guo, Juan; Shi, Linyuan; Wang, Jinye; Huang, Luqi; Wang, Sheng; et al. (Frontiers in Plant Science, 2023)
Shikonin derivatives are natural naphthoquinone compounds and the main bioactive components produced by several boraginaceous plants, such as Lithospermum erythrorhizon and Arnebia euchroma. Phytochemical studies utilizing both L. erythrorhizon and A. euchroma cultured cells indicate the existence of a competing route branching out from the shikonin biosynthetic pathway to shikonofuran. A previous study has shown that the branch point is the transformation from (Z)-3’’-hydroxy-geranylhydroquinone to an aldehyde intermediate (E)-3’’-oxo-geranylhydroquinone. However, the gene encoding the oxidoreductase that catalyzes the branch reaction remains unidentified. In this study, we discovered a candidate gene belonging to the cinnamyl alcohol dehydrogenase family, AeHGO, through coexpression analysis of transcriptome data sets of shikonin-proficient and shikonin-deficient cell lines of A. euchroma. In biochemical assays, purified AeHGO protein reversibly oxidized (Z)-3’’-hydroxy-geranylhydroquinone to produce (E)-3’’-oxo-geranylhydroquinone followed by reversibly reducing (E)-3’’-oxo-geranylhydroquinone to (E)-3’’-hydroxy-geranylhydroquinone, resulting in an equilibrium mixture of the three compounds. Time course analysis and kinetic parameters showed that the reduction of (E)-3’’-oxo-geranylhydroquinone was stereoselective and efficient in presence of NADPH, which determined that the overall reaction proceeded from (Z)-3’’-hydroxy-geranylhydroquinone to (E)-3’’-hydroxy-geranylhydroquinone. Considering that there is a competition between the accumulation of shikonin and shikonofuran derivatives in cultured plant cells, AeHGO is supposed to play an important role in the metabolic regulation of the shikonin biosynthetic pathway. Characterization of AeHGO should help expedite the development of metabolic engineering and synthetic biology toward production of shikonin derivatives.